Cuidador familiar do idoso dependente: estudo do perfil sócioeconômico e de saúde - Novembre, Rosângela Cláudia (2006)
The present research about family caregivers of dependent elderly was based on the overall increase of chronic-degenerative diseases with loss of independence and autonomy. Family caregiving in Brazil has become increasingly important over the years. Although the whole family is generally affected, caregiving is usually carried out by only one family member who undertakes the caregiving activities. As a result, many family caregivers face problems that jeopardize their health due to the overload of work and lack of caregiving skills. The chief objective of this study was to identify the profile of family caregivers of elderly persons admitted to the Mandaqui General Hospital in São Paulo. Research was conducted in two stages. Firstly, we interviewed 107 elderly patients at the hospital, 25 of whom were singled out as needing home care upon discharge. In the second phase, we sought to make contact with those patients family members who would act as caregivers. The research included six female caregivers aged 27-77 years old, with low education, good health conditions, and a restricted social life. The interviews revealed that family caregivers deserve particular attention as they are often unprepared to cope with the illness of an elderly family member for a prolonged period of time. The results of this study provided a social, economic and health profile of family caregivers, which was further presented to the Elderly Care Center of the São Paulo State Health Department